Qualidade das águas superficiais e avaliação do estado trófico do Rio Arari (Ilha de Marajó, norte do Brasil) - ALVES, Igor Charles Castor (Instituto Nacional de Pesquisas da Amazônia, 2014)
The deterioration of the water quality may be caused either by the result of human pressure on aquatic environments in larger scales, or by natural factors in smaller scales, such as part of the Arari River basin (Marajó Island, Pará state, Brazil) .This work aimed to evaluate the surface water's quality and the trophic state of the Arari River, between Santana and Cachoeira do Arari localities, taking into account the seasonal and spatial variations of physical, chemical and biological parameters in two different hydrological periods in 2009: the maximum discharge (April to May) and minimum discharge (September to November). The Water Quality Index (WQI) and Trophic State Index (TSI) were determined simultaneously in water surface's samples collected during 12 consecutive hours in three stations along the Arari River. The WQI data ranged from "Poor" and "Regular" and are probably related to the high levels of fecal coliform, low concentrations of dissolved oxygen and acid pH of the Arari River. Regards the TSI, the river may be classified as "supereutrophic" and "hipereutrophic", indicating the wide availability of nutrients (e.g. phosphorus) and high phytoplankton biomass in terms of chlorophyll a content. The Arari River is under a natural eutrophication, since the sources of anthropic contamination are still incipient, although they may contribute to the long-term process of artificial eutrophication.